Functions of Armenology in the Era of Globalization - Khoudinian , Gevorg (History and Culture, 2025)
Currently, Armenology has turned into a scientific worldview based on an integral understanding of the results of specific sciences about Armenia and Armenians, which, of course, does not have its own theory and method, but in a new competitive environment it can overcome foreign views about Armenia and Armenians formed from the outside by way of transformation of the Armenian view integrated within the independent state. Therefore, the task of the state operating in a new competitive environment is to form a management system of Armenology, an Armenology system, in order to scientifically substantiate and solve the tasks of self-knowledge, self-preservation, self-reproduction and self-expression of both its own citizens and at an appropriate level.Until now, Armenology had four main functions: scientific-cognitive, didactic-educational, formation of values ​​and development on its own basis, and protection and propaganda. In the present article, we have come to the conclusion that a fifth, civilizing function should be added to them. The reason is that the discovery and consolidation of the historical nucleus of Indo-Europeans, from India and Iran to the Romano-Germanic world, can resist the "Turan" project, which has been challenging the world civilization for a long time, which will allow to neutralize the opportunities of the Turan project to become a global region. Such a perspective has its geopolitical and economic aspect, the India – Iran – Armenia – Georgia - Europe communication axis, which, can be considered as a scientific task of discovering the cultural commonalities of the Indo-European or Aryan peoples.
Keywords: Armenology; globalization; historical necessity; historical comparative method; clinical death; cognitive war; progressive goals; global region; civilizational function